An Optical/Ferroelectric Multiplexing Multidimensional Nonvolatile Memory from Ferroelectric Polymer. Issue 24 (12th May 2022) - He, Shan; Guo, Mengfan; Wang, Yue; Liang, Yuhan; Shen, Yang
Abstract: Multiplexing physical dimensions to realize multidimensional storage in a single material has been a goal to increase storage density and data security. Multidimensional storage is only achieved in optical storage material (OSM) by far. Poly(vinylidene fluoride) (PVDF), a semicrystalline polymer, is widely studied as a candidate for ferroelectric random access (FeRAM). Herein, the atomic force microscopy (AFM)‐based infrared spectroscopy techniqueis used to induce multilevel phase transformations in PVDF ultrathin film on nanometric scales and for writing/readout of IR signals. An optical/ferroelectric multiplexing PVDF memory, where information can be coded with independent four‐level optical IR and bilevel ferroelectric signals, is demonstrated. High data security and a storage density up to 180 GBit in. −2 are achieved simultaneously. Owing to the different critical temperature for phase transformation (optical data, <167 °C) and polarization switching (ferroelectric data, <100 °C), the multiplexing memory can function both as optical read‐only memory and FeRAM. This work expands material supporting physical dimensions multiplexing beyond OSM for the first time, opening up new opportunities for future high‐capacity, multifunctional nano‐memory. The strategy proposed here enables on‐demand and tunable programming on IR waves, offering prospects for fabrication of active nano‐optical devices. Abstract : By using atomic force microscopy (AFM)‐based infrared spectroscopy as a nano‐optical writing/readout tool, a novel optical/ferroelectric multiplexing poly(vinylidene fluoride) memory with independent four‐level optical and bilevel ferroelectric signals is demonstrated. The different temperature tolerance of phase change and polarization switching enables an integration of optical read‐only memory and ferroelectric random access. This work opens up new opportunities for high density and security data storage.